Concurrency control in distributed databases through time intervals and short-term locks - Halici, U.; Dogac, A. (IEEE transactions on software engineering, 1989)
A method for concurrency control in distributed database management systems that increases the level of concurrent execution of transactions, called ordering by serialization numbers (OSN), is proposed. The OSN method works in the certifier model and uses time-interval techniques in conjunction with short-term locks to provide serializability and prevent deadlocks. The scheduler is distributed, and the standard transaction execution policy is assumed, that is, the read and write operations are issued continuously during transaction execution. However, the write operations are copied into the database only when the transaction commits. The amount of concurrency provided by the OSN method is demonstrated by log classification. It is shown that the OSN method provides more concurrency than basic timestamp ordering and two-phase locking methods and handles successfully some logs which cannot be handled by any of the past methods. The complexity analysis of the algorithm indicates that the method works in a reasonable amount of time.< >